Pro SQL Server 2005 Assemblies - Dewson, Robin (Apress, 2012)
The bulk of this book consists of chapters that walk you through how to build each type of SQL Server assembly. In each case, we provide carefully chosen examples that demonstrate business problems where assemblies could be of true benefit. For example, we show how .NET greatly simplifies working with images and XML data, and accessing external data sources and web services. We also devote chapters to debugging and error handling strategies in SQL Server assemblies and to their security implications.